2018
DOI: 10.1186/s12884-018-1807-0
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of U.S. Hispanic and non-Hispanic women toward congenital CMV prevention behaviors: a cross sectional study

Abstract: BackgroundCongenital cytomegalovirus (CMV) infection is the most common intrauterine infection. The only way to protect against congenital CMV infection is to practice CMV prevention behaviors. CMV seroprevalence rates are high in Hispanic women. It is unknown whether communication strategies should differ by ethnicity. The purpose of this study was to understand differences between U.S. Hispanic and non-Hispanic women’s attitudes toward CMV prevention behaviors and examine the relationship between perceived s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Treatment and interventions for children with cCMV have changed, adding on time sensitivity to discuss diagnostic testing and use of antivirals. Additionally, though general public and provider awareness continues to remain low [ 5 , 7 , 8 , 25 ], several U.S. states have enacted legislation to increase CMV awareness, implement hearing-targeted CMV screening, or both, starting in 2013 [ 23 ]. Further research is needed to understand parental perceptions and communication needs within the context of more contemporaneous screening programs for cCMV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment and interventions for children with cCMV have changed, adding on time sensitivity to discuss diagnostic testing and use of antivirals. Additionally, though general public and provider awareness continues to remain low [ 5 , 7 , 8 , 25 ], several U.S. states have enacted legislation to increase CMV awareness, implement hearing-targeted CMV screening, or both, starting in 2013 [ 23 ]. Further research is needed to understand parental perceptions and communication needs within the context of more contemporaneous screening programs for cCMV.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the serious consequences that can result with cCMV, studies have reported low knowledge and frequency of cCMV counseling among obstetric specialists and, among pediatric general providers, mixed knowledge and low comfort with caring for children with cCMV [ 5 , 6 ]. Other studies have reported that knowledge about cCMV is low amongst expectant parents [ 7 , 8 ], and that parents of children who have cCMV emphasized that they would have benefitted from clear guidance and support post-diagnosis and information about cCMV prevention during pregnancy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%